Engineering of Escherichia coli for D-allose fermentative synthesis from D-glucose through izumoring cascade epimerization - Zheng, Ling-Jie; Guo, Qiang; Zhang, Ya-Xing; Liu, Chen-Yang; Fan, Li-Hai; Zheng, Hui-Dong (Frontiers in Bioengineering and Biotechnology, 2022)
D-Allose is a potential alternative to sucrose in the food industries and a useful additive for the healthcare products in the future. At present, the methods for large-scale production of D-allose are still under investigation, most of which are based on in vitro enzyme-catalyzed Izumoring epimerization. In contrast, fermentative synthesis of D-allose has never been reported, probably due to the absence of available natural microorganisms. In this work, we co-expressed D-galactose: H+ symporter (GalP), D-glucose isomerase (DGI), D-allulose 3-epimerase (DAE), and ribose-5-phosphate isomerase (RPI) in Escherichia coli, thereby constructing an in vivo Izumoring pathway for yielding D-allose from D-glucose. The carbon fluxes and carbon catabolite repression (CCR) were rationally regulated by knockout of FruA, PtsG, Glk, Mak, PfkA, and PfkB involved in the pathways capable of phosphorylating D-fructose, D-glucose, and fructose-6-phosphate. Moreover, the native D-allose transporter was damaged by inactivation of AlsB, thus driving the reversible Izumoring reactions towards the target product. Fermentation was performed in the M9 medium supplemented with glycerol as a carbon source and D-glucose as a substrate. The results show that the engineered E. coli cell factory was able to produce approximately 127.35 mg/L of D-allose after 84 h. Our achievements in the fermentative production of D-allose in this work may further promote the green manufacturing of rare sugars.